The nine secrets of women who get what they want - White, Kate (Arrow Books, 1999)
Kate White's nine strategies, simply and wittily explained, provide a guide to feminine success. Adopt the approach, and watch your career go into orbit as colleagues wonder at the new you whose tenacity, energy and sheer drive forces everybody to sit up and take notice.